1982
DOI: 10.1149/1.2123803
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Studies of Li‐Ge Alloys: Application to Negative Electrodes for Molten Salt Batteries

Abstract: The use of germanium as an alloying agent for lithium negative electrodes in molten salt cells was studied in a cell of the typeLiAl46.8 wt%LiClLi‐Ge53.2 wt%KClAlloybetween 360° and 440°C. The Li‐Ge electrode could be charged and discharged reversibly with lithium. Five distinct two‐phase plateau regions, together with a suspected sixth region, were identified by coulometrically charging and discharging the cell. The five distinct two‐phase plateau regions are believed to occur during the formation of normalL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 4 publications
3
8
0
Order By: Relevance
“…Since the voltage is given by the reaction energy divided by the charge, from Figure b, we infer that dilute Li insertion into p-type Ge occurs at energies of −0.6 to −0.4 eV, corresponding to a voltage of 0.4–0.6 V at dopant concentrations of <10 21 cm –3 (a condition satisfied in the doped wafers used in our experiments). In comparison, total energy calculations of the bulk crystalline LiGe and Li 9 Ge 4 phases give formation energies of −0.57 and −0.44 eV per Li, corresponding to lithiation voltages of 0.57 and 0.44 V, respectively, in good agreement with voltage plateaus for corresponding phases measured at 400 °C . Since the initial voltage for bulk Li x Ge formation is similar to that of dilute Li insertion into p-type Ge, the dopant effects on onset voltage in Ge should be small.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Since the voltage is given by the reaction energy divided by the charge, from Figure b, we infer that dilute Li insertion into p-type Ge occurs at energies of −0.6 to −0.4 eV, corresponding to a voltage of 0.4–0.6 V at dopant concentrations of <10 21 cm –3 (a condition satisfied in the doped wafers used in our experiments). In comparison, total energy calculations of the bulk crystalline LiGe and Li 9 Ge 4 phases give formation energies of −0.57 and −0.44 eV per Li, corresponding to lithiation voltages of 0.57 and 0.44 V, respectively, in good agreement with voltage plateaus for corresponding phases measured at 400 °C . Since the initial voltage for bulk Li x Ge formation is similar to that of dilute Li insertion into p-type Ge, the dopant effects on onset voltage in Ge should be small.…”
supporting
confidence: 65%
“…Because of these similarities, one might expect crystalline Si and Ge to have similar electrochemical properties upon lithiation. Indeed, at high temperatures (∼400 °C), both Si and Ge lithiate to form similar crystalline Li x Si/Li x Ge zintl phases in several voltage steps. At room temperature, however, the formation of most ,,, such phases is suppressed, and lithiation leads first to amorphization and eventually to the formation of the isostructural crystalline Li 15 Si 4 or Li 15 Ge 4 ,, phases.…”
mentioning
confidence: 99%
“…High-capacity anode materials will allow for a diminution of the amount of active material required in the cell, thereby decreasing the weight and cost of a commercial battery. Prior to battery efforts, researchers studied the kinetics of lithium diffusion in germanium because semiconducting materials were convenient for measuring resistivity and maintaining stable dislocations. At 400 °C, there are several thermodynamically accessible, electrochemically reversible Ge–Li alloy phases, including LiGe, Li 9 Ge 4 , and Li 15 Ge 4 , that form under chronopotentiometric conditions . More recently, the mechanism of lithium (de)­insertion in silicon at room temperature has been studied by pair distribution function analysis and solid-state NMR spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…These materials store lithium through the formation of a bulk lithiated alloy and have capacities several times that of graphite. The thermodynamic limits for lithium alloy formation have been found to be Li 22 X 5 (X = Si,Ge) which represents 4200 mAh g –1 for Si, and 1624 mAh g –1 for Ge; these capacities have been realized at elevated temperatures, but studies on electrochemical lithiation of silicon at room temperature have shown that the highest accessible state is Li 15 Si 4 , which still represents a capacity of 3579 mAh g –1 . , There is still confusion about the accessible capacity for germanium. Baggetto et al .…”
mentioning
confidence: 99%